Chapter Spatial configurations and flows in the morphogenetic processes of settlements. A planning experience on the Tuscan coast. - Saragosa, Claudio (Proceedings e report, 2020)
The effects of climate change are appearing before us and show the fragility of settlements that are no longer able to manage natural phenomena and therefore their increasingly effect on them. The process of morphogenesis of cities has sedimented spatial configurations, which over time have lost the ability to manage a dynamic balance with the metabolism of the reference environment. The contribution presents a research study aimed at the planning of the Tuscan coast, in which, a novel methodology is proposed for the regeneration of patterns no longer able to manage the current metabolic flows.